Influence of peritoneal dialysis solution biocompatibility on long-term survival of patients on continuous ambulatory peritoneal dialysis and the technique itself - Stanković-Popović Verica; Popović Dragan; Dimković Nada; Maksić Đoko; Vasilijić Saša; Čolić Miodrag; Vučinić Žarko; Rađen Slavica; Miličić Biljana (Vojnosanitetski Pregled)
Background/Aim. Morbidity and mortality of continous ambulatory peritoneal dialysis (CAPD) patients is still very high. The aim of the study was to evaluate the effects of peritoneal dialysis (PD) solutions (standard vs biocompatible) on long-term patients’ and the techique survival. Methods. A total of 42 stable patients on CAPD participated in this crosssectional study. They were prospectively followed-up during the twelve years. Patients with severe anemia (Hb < 10 g/L) and malignant disease ware excluded. Twenty one (50%) patients were treated with the standard PD solutions (CAPDP- 1) while the other 21 (50%) were treated with biocompatible PD solutions [(lower level of glucose degradation products, lower concentration of Ca2+ and neutral pH (CAPDP-2)]. All patients were analyzed for a presence of vascular calcification, nutrition status, and parameters of inflammation after 2.5 ± 0.6 years of starting CAPD, and these variables considered in the analysis as risk factors. Results. The patients from the group CAPDP-2 compared to those from the group CAPDP-1 had lower level of high-sensitivity C-reactive protein (hs-CRP) (p = 0.003), and better nutritional status as confirmed by the mid-arm circumference (p = 0.015), and midarm muscle circumference (p = 0.002) and subjective global assessment (p = 0.000). Also, they had lower vascular calcifications as confirmed by intima media thickness (IMT) (p = 0.003), degree of carotid narrowing (p = 0.001) and calcified plaques of common carotid arteries (CCA) (p = 0.008). Kaplan- Meier analysis confirmed better survival of patients from the group CAPDP-2 than those from the group CAPDP-1 (1-, 5-, and 10-year patients survival rate was: 100%, 61.9% and 14.3% for the group CAPDP-1, and 100%, 85.7%, and 52.4% for the group CAPDP-2, respectively; p = 0.0345). The 1-, 5-, and 10-year technique survival rate was: 100%, 71.4%, and 38.1% for the group CAPDP-1, and 100%, 85.7%, and 76.2% for the group CAPDP-2, respectively; (p = 0.0719). Duration of dialysis, serum triglyceride and cardiovascular score (quantitative scoring system consisting of: ejection fraction (EF) of left ventricle < 50%; IMT > 1 mm; carotid narrowing degree > 50%, presence of carotid plaques in both common carotide, ischaemic heart disease, cerebrovascular event and peripheral vascular disease with or without amputation) were independent predictors of overall patient survival. Duration of dialysis was only independent predictor of overall technique survival. Conclusion. Although patients treated with biocompatible solutions showed significantly better survival, the role of biocompatibility of CAPD solutions in patients and technique survival have to be confirmed. Namely, multivariate analysis confirmed that duration of dialysis, serum triglyceride and cardiovascular score significantly predicted overall CAPD patients survival, while only duration of dialysis was found to be independent predictor of overall techique survival.